Accounting deviations between the measured and simulated impact pressures in high-density snow avalanches - Rakesh K. Aggarwal; Ranjan Das; Hemendra S. Gusain (Arctic, Antarctic, and Alpine Research)
Most of the available models for estimating the snow avalanche impact pressures are 2D in nature. In this work, a 3D non-Newtonian Navier-Stokes equations–based simulation model is developed. For transient comparison, snow avalanche impact pressures were measured on an instrumented obstacle of 1 m height and 0.65 m width for high-density moist snow. This experimental setup was developed and installed on a 61-m-long facility at a research station near Manali, Himachal Pradesh, India. Based on experimentations and simulations carried out in the current work, the measured and simulated avalanche impact pressures were correlated, which can be used to estimate the avalanche impact pressures on the structures for the dense flow of avalanches. The root mean square error between the currently proposed model and the measured data is nearly 10.74, which is significantly less than the existing models for the estimation of the avalanche impact pressures on the obstacles. Further, the effective drag coefficient [Formula: see text] for the avalanche flow and the instrumented obstacle, which takes into account the combined effects of the fluid, solid, granular, and compressibility effects of the flowing snow, is found in the range of 3.97 to 8.54, which is in agreement with published studies.